The potential of using hair cortisol to measure chronic stress in occupational healthcare; a scoping review - Schaafsma, Frederieke G. (J Occup Health, 2021)
OBJECTIVES: Workplace‐based selective prevention of mental health problems currently relies on subjective evaluation of stress complaints. Hair cortisol captures chronic stress responses and could be a promising biomarker for the early identification of mental health problems. The objective was to provide an overview of the state‐of‐the‐art knowledge on the practical value of hair cortisol in the occupational setting. METHODS: We performed a scoping review of cross‐sectional and longitudinal studies in PubMed, Embase, and PsycINFO up to November 2019 assessing the relations of hair cortisol with work‐related stressors, perceived stress, and mental health outcomes in healthy workers. RESULTS: We found five longitudinal studies, of which two observed an increase in work‐related stressors to be associated with higher hair cortisol, one found a relation with lower hair cortisol and one did not find a relationship. Findings of cross‐sectional studies were also mixed. The one available longitudinal study regarding mental health showed that hair cortisol was not related to depressive symptoms. CONCLUSIONS: Hair cortisol measurement within occupational health research is still in its early stage and more longitudinal studies are urgently needed to clarify its relationship with work‐related stressors and perceived stress before hair cortisol can be used to identify workers at risk for mental health problems.